Persekusi Sebagai Pelanggaran Hak Hidup Menurut Hukum Internasional (Kasus Persekusi oleh Taliban di Afganistan) - Giovanny Pricillia Huwae; Johanis Steny Franco Peilouw; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The withdrawal of United States troops from Afghanistan caused pros and cons in the world community. Their fears of a return to a Taliban Government that implements hardline Islamic Sharia law have forced Afghans to flee their country en masse. The Taliban are famous for their acts of persecution against the weak or miniroties who are considered to disagree with them.Purposes of the Research: The purpose of writing this journal is to find out international legal arrangements regarding persecution which is a violation of the right to life and also to know that the persecution by the Taliban violates human rights. The method used in the research is a normative research method. Methods of the Research: The type of research used is the type of normative legal research, and uses a statutory approach, case approach and conceptual approach. The legal materials used primary and secondary legal materials which are classified and arranged systematically and then reviewed to answer the problems under study.Results of the Research: The result of this research is that persecution is an act of violation of the right to life as regulated in the third article of the Universal Declaration of Human Rights in 1948, and is one of the international crimes against humanity regulated in the Rome Statute in 1998. Rough and brutal acts carried out by the Taliban are acts of persecution that violate of human rights. In the Universal Declaration of Human Rights, the third article and the eleventh article, the first paragraph emphasizes that everyone has the right to life and cannot be killed arbitrarily and cannot be punished before a court decision is made on charges of wrongdoing.